PERBEDAAN SUMBER INFORMASI, DUKUNGAN SUAMI, DAN DUKUNGAN TENAGA KESEHATAN PADA PENGETAHUAN IBU PRIMIGRAVIDA DALAM MENGATASI KETIDAKNYAMANAN SELAMA HAMIL DI PMB M BOGOR - Dwi Rachmah Yuniarti; Yulia Herawati; Emilia (JURNAL KESEHATAN DAN KEBIDANAN, 2022)
ABSTRACT Pregnant women who do not have knowledge about their discomforts during pregnancy are more likely can not resolves their discomforts during pregnancy, because behaviors based on knowledge will be more lasting than behaviors that are not based on knowledge. The purpose of this study was to determine the information sources, husband’s support, and health workes’s support on the knowledge of primigravida mothers in resolves discomfort during pregnancy at PMB M Bogor in 2020 The research method used was descriptive analytic design with a cross sectional approach, the type of research used quantitative metodh. The sampling technique in this research uses total sampling. The results showed that there was no difference in maternal knowledge in resolving discomfort during pregnancy based on information sources (p-value = O, 805), and husband's support (p-value = 0.469). Meanwhile, there are difference in maternal knowledge in resolving discomfort during pregnancy based on the support of health workers (p-value = 0.04). This research is expected to be useful as a reference or reference for lecturers and students to continue this research into better research. This research is expected to be useful for service providers in the place concerned by providing input in order to improve health services for pregnant women as optimally as possible. Keywords: Knowledge, Information Sources, Husband's Support, Health Worker’s Support